2019
DOI: 10.1007/s12144-019-00315-9
|View full text |Cite
|
Sign up to set email alerts
|

Would you be happier if you moved more? Physical activity focusing illusion

Abstract: Research shows that individuals who are more physically active also report greater happiness. However, subjective well-being is prone to cognitive biases. For instance, people overrate the influence of single factors (e.g., money) on their happiness; a phenomenon termed the focusing illusion. In this study, we examined whether the relationship between physical activity and subjective well-being is stronger when individuals focus on physical activity explicitly compared to individuals with no specific focus. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, studies addressing the associations between LS and VPA among adolescents are rare. The long-term contribution of VPA on higher LS, when compared with moderate PA, was confirmed by Kaczmarek et al [ 45 ], but only in students aged 18 to 45 years. Lithuanian authors Slapšinskaitė, Lukoševičiūtė, and Šmigelskas [ 2 ] considered VPA in boys to be a predictor of better life satisfaction, whereas in girls, moderate-to-vigorous PA (MVPA) was considered to be a risk factor for lower LS.…”
Section: Discussionmentioning
confidence: 71%
“…However, studies addressing the associations between LS and VPA among adolescents are rare. The long-term contribution of VPA on higher LS, when compared with moderate PA, was confirmed by Kaczmarek et al [ 45 ], but only in students aged 18 to 45 years. Lithuanian authors Slapšinskaitė, Lukoševičiūtė, and Šmigelskas [ 2 ] considered VPA in boys to be a predictor of better life satisfaction, whereas in girls, moderate-to-vigorous PA (MVPA) was considered to be a risk factor for lower LS.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, Smith, Monnat and Lounsbery [5] reported that 17% of PE time was spent in VPA. Increasing the step count in PE lessons in shorter time intervals can significantly increase VPA in PE lessons, and can thus promote it to obtain stable well-being benefits [51]. There is a declining trend in the positive evaluation of PELs in the Czech Republic, especially among girls [30].…”
Section: Discussionmentioning
confidence: 99%
“…PG affects mild-intensity physical activity in particular compared to other physical activity intensities (Nigg, Mateo, & An, 2016). This limits the impact of PG gaming because high-intensity physical activity has some unique effect on physiology, e.g., secretion of endorphins that inhibit pain signals (Boecker et al, 2008;McGowan et al, 1991), and wellbeing (Kaczmarek et al, 2019). There is also evidence that the initial boost in physical activity is likely to be gradually attenuated within the next three to six weeks of playing PG (Howe et al, 2016;Liu & Ligmann-Zielinska, 2017;Ma et al, 2018).…”
Section: Physical Symptomsmentioning
confidence: 99%